2002
DOI: 10.1002/1521-4141(200205)32:5<1264::aid-immu1264>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of chemokine receptor expression and chemotactic responsiveness during differentiation of human naive T cells into Th1 or Th2 cells

Abstract: Chemokines and their receptors direct movements and encounters of lymphocytes and professional APC into specific microenvironments of lymphoid tissues. Chemokine receptors such as CCR7, CXCR5 and CCR4 that are differentially expressed and modulated in distinct subsets of T cells contribute to establish functionally and spatially segregated microenvironments within secondary lymphoid tissues where T cell activation and differentiation occur. Here, we have explored the modulation of CCR7, CCR4, CCR8 and CXCR5 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…The polarization of T cells into Th1 and Th2 cells is associated with their expression of different subsets of chemokine receptors (51). The CD4 ϩ T cells isolated from intranasally OmpA immunized mice express increased levels of CCR5, whereas there has been no significant induction in the expression of CCR3, CCR4, and CXCR3.…”
Section: Discussionmentioning
confidence: 99%
“…The polarization of T cells into Th1 and Th2 cells is associated with their expression of different subsets of chemokine receptors (51). The CD4 ϩ T cells isolated from intranasally OmpA immunized mice express increased levels of CCR5, whereas there has been no significant induction in the expression of CCR3, CCR4, and CXCR3.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with reports indicating expression of CCR8 on in vitro differentiated and activated Th2 cells (23,24,48). We also found that levels of secreted IL-17 are far greater in the CCR8 Ϫ population.…”
Section: Discussionsupporting
confidence: 94%
“…Isolated T cells were plated onto 96-well plates precoated with anti-CD3 mAb and anti-CD28 mAb (eBioscience, USA) [47]. Cultures were supplemented with 1 mg/mL rHMGB1 (H4652, Sigma Aldrich, USA), at 24, 48, 72, and 96 h. When cells were recovered, Th17-cell polarization was assessed as previously described, using 50 ng/mL PMA and 1 mg/mL ionomycin [51] (both from Sigma Aldrich). GolgiPlug (BD Pharmingen, USA) was added during the last 5 h of culture to prevent cytokine secretion.…”
Section: Facs Analysismentioning
confidence: 99%